Changes in, and predictors of, quality of life among patients with unstable angina after percutaneous coronary intervention. Issue 2 (16th June 2020) - Van Nguyen, Huy; Khuong, Long Quynh; Nguyen, Anh Tuan; Nguyen, Anh Le Tuan; Nguyen, Cham Thi; Nguyen, Ha Thi Thu; Tran, Thu Thi Ha; Dao, An Thi Minh; Gilmour, Stuart; Van Hoang, Minh
Abstract: Rationale, aims and objectives: Changes in, and predictors of, quality of life (QoL) among unstable angina patients are informative for both clinical and public health practice. However, there is little research on this topic, especially in health care settings with limited resources. This study aims to detect changes in QoL and its associated factors among patients with unstable angina after percutaneous coronary intervention. Methods: A longitudinal design was conducted with two repeated rounds of measurements, 1 and 3 months after intervention, using the generic SF‐36 questionnaire, in 120 patients from Vietnam National Heart Institute. A linear mixed‐effects model was used to assess changes in patient QoL over time while adjusting for other covariates. Results: Only two out of eight QoL subscales (social functioning and emotional well‐being) declined after 1 month, but these tended to rise again after 3 months, while scores of all other QoL subscales increased. Adjusting for covariates, QoL increased slightly after 1 month of intervention ( β = 0.65, 95%CI = −0.86 to 2.16) but improved by almost six QoL points after 3 months ( β = 5.99, 95%CI = 4.48 to 7.50). Four confounders significantly associated with a decline in QoL were older age, being retired, living in rural areas, and having abnormal troponin level. Conclusion: QoL of the patients with unstable angina improves significantly 3 months after intervention, rather than after 1 month. More attention should be given to patients, who are old, retired, live in rural areas and have abnormal troponin level.